(untitled) (Journal of the College of Basic Education, 2025)
The current research discusses one of the most common problems that black people in the United States suffer from: the dual presence of the past (through memory) and the present, through which the realities of immigration and racism are revealed in the novel Roots by Alex Haley. The author was able to criticize the colonial practices that took place in the nation of his ancestry by making use of memory, which reenacts the past with all of its traumas. This novel offers an insightful investigation of memory traumas, past hurts, and what Africans went through in their lives. As an African American writer, he articulates the experiences related to racial prejudice, frustration, and identity crises that are encountered by individuals of black descent. Trauma generally refers to a mental condition that develops in response to the terrifying experience of a violent and extremely traumatic incident. These events can be physically or psychologically harmful or both and has a profound impact on a person’s mental makeup over a long period of time as it impairs their ability to distinguish between the past and the present. The study follows the psychological approach to analyses trauma in the novel. Using the concept of trauma theory from a psychological perspective to explain the condition of the characters in the novel. The research aims to trace the psychological effects of terrorism, discrimination, and identity diaspora and their impact on collective memory. The research may reveal that painful experiences profoundly alter characters’ identities and self-perception, illustrating the impact of historical tragedy on personal narratives. While all the laws prohibit these are abnormal phenomena, as it has negative effects that harm the societies, regardless of shape, color, and even the beliefs. This research came to shed light on the most important issues of these delicate matters.